Mechanism and synthesis - Clark, Giles; University, The Open.; Taylor, P G.; Smart, Lesley E. (U.K Royal Society of Chemistry, 2003)
This book pursues possible strategies for synthesising mainly organic compounds, particularly those of interest to the health sector and related industries. Topics covered include addition reactions of aldehydes and ketones; the use of organometallic reagents to form carbon-carbon bonds (eg Grignard reagents); and radical reactions, including selectivity and chain reactions. Retrosynthetic analysis is introduced as a strategy for developing syntheses, along with biochemical pathways. Mechanism and Synthesis concludes with a Case Study on polymers, which demonstrates how chain reactions can be used to build up useful materials with specific properties, such as contact lenses. The Molecular World series provides an integrated introduction to all branches of chemistry for both students wishing to specialise and those wishing to gain a broad understanding of chemistry and its relevance to the everyday world and to other areas of science. The books, with their Case Studies and accompanying multi-media interactive CD-ROMs, will also provide valuable resource material for teachers and lecturers. (The CD-ROMs are designed for use on a PC running Windows 95, 98, ME or 2000.)